An assessment of risk factors for early death among a sample of previously incarcerated youth - Mallett, Christopher A. (2014)
Most previous research regarding early death prior to, or during, young adulthood among previously detained delinquent youth has focused predominantly on males or on their cause of death. This study extends previous research by evaluating potential factors that are associated with early death in a random sample (N = 999) of formerly detained youthful offenders in New York stratified by gender (50% female). Existing case records were referenced with the National Death Index to determine if the formerly detained youth were deceased by the time they would have reached age 28. Regression analyses were run to determine if any of 16 sociodemographic, offense history, weapons/gang involvement, mental health, substance use, child maltreatment, child welfare, or family environmental risk factors measured in their childhood or adolescence were associated with early death. Two additional regression analyses were run to determine if those risk factors differentially impacted early death for males vs. females. Of the variables measured, however, only gender was significantly related to early death – compared to females, males were 2.3 times more likely to have prematurely died. Additionally, in the model run separately for females, being an African-American female was protective against early death. These findings are compared to findings from the existing literature